Waterborne polyurethane wear-resistant coating and preparation method thereof

By introducing specific components into the aqueous polyurethane coating and building a composite coating, the problem of water-based polyurethane coatings being easily swelled or degraded under a chemical environment is solved, and the ultra-wear, impact and chemical resistance of the coating is achieved.

CN119859463AActive Publication Date: 2025-04-22YUEYANG JINGWEI NEW MATERIALS CO LTD

Patent Information

Application Number
CN202510166352.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-02-14
Publication Date
2025-04-22
Estimated Expiration
2045-02-14

AI Technical Summary

Technical Problem

Water-based polyurethane coatings are prone to swelling or degradation under chemical environments, and hydrophilic groups in their aqueous systems may lead to a decrease in the mechanical properties of the coating film, limiting its application in harsh environments.

Method used

By introducing components such as polytetrafluoroethylene, fluorinated modified nanosilica, aminoglycene, nanocellulose and hexamethylene diisocyanate into aqueous polyurethane coatings, a composite coating with ultra-wear resistance, superhydrophobicity and high mechanical stability is constructed.

Benefits of technology

The coating is ultra-wear, impact and chemical resistance, which significantly improves its application performance in harsh environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119859463A_ABST
    Figure CN119859463A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of coatings, and particularly relates to a waterborne polyurethane wear-resistant coating and a preparation method thereof. The waterborne polyurethane wear-resistant coating is prepared from the following raw materials in parts by weight: 65 to 75 parts of waterborne polyurethane, 5 to 10 parts of polytetrafluoroethylene, 3 to 6 parts of fluorinated modified nano silicon dioxide, 2 to 5 parts of aminated graphene, 2 to 3 parts of hexamethylene diisocyanate, 0.5 to 1 part of emulsifier and 1 to 3 parts of nano cellulose. The waterborne polyurethane is utilized to construct a stable main body frame under the HDI crosslinking effect, the polytetrafluoroethylene and the fluorinated modified nano silicon dioxide form a lasting super-hydrophobic and antifouling outer layer on the surface, and the aminated graphene and the nano cellulose provide tough mechanical support in the interior; due to the organic combination of the components, the coating has better impact resistance, chemical resistance and wear resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of coatings, and particularly relates to a waterborne polyurethane wear-resistant coating and a preparation method thereof. Background Art

[0002] Paint is one of the most widely used materials in modern industry and daily life. Its main functions include decoration, beautification and protection, providing physical and chemical barriers for a variety of substrates. However, traditional solvent-based paints release a large amount of volatile organic compounds (VOCs) and other harmful substances during use, which not only cause serious pollution to the environment, but also pose a significant threat to human health. With the continuous upgrading of environmental protection regulations and the enhancement of public environmental awareness, the global coatings industry is in a critical period of transformation from high pollution and high energy consumption to low pollution and low energy consumption. In response to increasingly stringent environmental protection requirements, the coatings industry is accelerating the application of water-based technology. Water-based paint uses water as the main solvent or dispersion medium. Compared with traditional solvent-based paints, it significantly reduces VOC emissions. At the same time, it has higher safety and convenient construction performance, becoming an important technical path to promote the green transformation of the coatings industry.

[0003] Among them, waterborne polyurethane coatings, as an environmentally friendly coating based on polyurethane dispersion, have attracted great attention in the market for their low VOC emissions, excellent mechanical properties and chemical stability. Compared with traditional solvent-based coatings, waterborne polyurethane coatings use water as a dispersion medium, which greatly reduces pollution to the environment and harm to human health, and fully complies with global sustainable development goals and strict environmental regulations. From the performance characteristics, the molecular structure of waterborne polyurethane coatings consists of soft segments and hard segments, with highly adjustable physical properties. The soft segment gives the coating film good flexibility, while the hard segment provides excellent mechanical strength and wear resistance, making it perform well under external friction and impact conditions. This characteristic makes waterborne polyurethane coatings widely used in high-demand industrial, household and construction fields. In addition, its low flammability characteristics significantly improve the safety of the coating during production, transportation and construction. The construction method is flexible and can be completed through a variety of processes such as spraying and brushing, and is suitable for a variety of substrates. Although waterborne polyurethane coatings have many advantages, the hydrophilic groups in its water-based system may lead to a decrease in the mechanical properties of the coating film. At the same time, in chemical environments such as acid, alkali or solvent, waterborne polyurethane coatings are prone to swelling or degradation, limiting their application in harsh environments. These problems have become the main technical bottlenecks for the further development of waterborne polyurethane coatings. Therefore, based on the above problems, it is extremely necessary to develop a waterborne polyurethane coating that is chemically resistant, impact resistant and wear resistant. Summary of the invention

[0004] In view of the defects of the prior art, the object of the present invention is to provide a waterborne polyurethane wear-resistant coating and a preparation method thereof.

[0005] The technical effect described in the present invention is achieved through the following technical scheme: a water-based polyurethane wear-resistant coating, which comprises the following raw materials in parts by weight: 65 to 75 parts of water-based polyurethane, 5 to 10 parts of polytetrafluoroethylene, 3 to 6 parts of fluorinated modified nano-silica, 2 to 5 parts of amino graphene, 2 to 3 parts of hexamethylene diisocyanate, 0.5 to 1 part of emulsifier and 1 to 3 parts of nano-cellulose.

[0006] Preferably, the emulsifier is any one of Tween-20, sodium dodecylbenzene sulfonate and PEG-40.

[0007] Preferably, the specific preparation steps of the fluorinated modified nano-silica are as follows:

[0008] A1: Disperse nano-silicon dioxide in anhydrous ethanol, disperse evenly by ultrasonic treatment, and obtain nano-silicon dioxide dispersion; add trifluoropropyltriethoxysilane to anhydrous ethanol, stir and mix evenly, adjust the pH to 4-5 with 0.1M hydrochloric acid, and let stand for 30 minutes to obtain a silane solution;

[0009] A2: Slowly add the nano-silica dispersion prepared in step A1 to the silane solution, control the temperature at 40-60°C, stir and react for 4-6 hours, centrifuge, filter, wash alternately with anhydrous ethanol and deionized water for 3 times, and dry at 60-80°C for 12-24 hours to obtain fluorinated modified nano-silica;

[0010] Preferably, in step A1, the ratio of the amount of the nano-silicon dioxide to the amount of anhydrous ethanol is 20 mg: 1-2 mL; the ratio of the amount of the trifluoropropyltriethoxysilane to the amount of anhydrous ethanol is 1 g: 20-30 mL;

[0011] Preferably, in step A2, the volume ratio of the nano-silicon dioxide dispersion to the silane solution is 100:3-5.

[0012] Preferably, the specific preparation steps of the amination graphene are as follows:

[0013] B1: Graphene oxide was dispersed in deionized water, and dispersed evenly by ultrasonic treatment. Then, anhydrous ethanol was added and stirred for 10 minutes to obtain a graphene oxide dispersion.

[0014] B2: Add ethylenediamine to the graphene oxide dispersion prepared in step B1, adjust the pH to 10-11 with ammonia water, heat in a water bath to 80°C, stir and react for 6-8h. After the reaction is completed, cool naturally to room temperature, centrifuge, wash alternately with deionized water and anhydrous ethanol for 3 times, and dry at 60°C for 12-24h to obtain amination graphene;

[0015] Preferably, in step B1, the ratio of the amount of graphene oxide, deionized water and anhydrous ethanol is 1 g: 100-150 mL: 8-10 mL;

[0016] Preferably, in step B2, the volume ratio of the graphene oxide dispersion to ethylenediamine is 10-15:2.

[0017] Preferably, another aspect of the present invention is to provide a method for preparing a waterborne polyurethane wear-resistant coating, and the specific preparation steps are as follows:

[0018] Step 1: Disperse nanocellulose in deionized water, and ultrasonically disperse for 20 to 30 minutes to obtain a 3 to 5 wt% nanocellulose dispersion; disperse polytetrafluoroethylene in deionized water, and ultrasonically disperse for 10 to 20 minutes to obtain a 30 to 40 wt% polytetrafluoroethylene dispersion; add amino graphene to 90 wt% ethanol solution, and ultrasonically disperse for 20 to 30 minutes to obtain a 1.5 to 2 wt% amino graphene aqueous dispersion;

[0019] Step 2: Add the waterborne polyurethane to deionized water, dilute to 30-40 wt% solid content, add 0.5-2 wt% emulsifier, stir for 10 min, and obtain a waterborne polyurethane system; slowly dropwise add the polytetrafluoroethylene dispersion prepared in step 1 to the waterborne polyurethane system, and stir at 300-500 rpm for 20 min;

[0020] Step 3: After completing the operation in step 2, add fluorinated modified nano-silica, continue to stir at 300-500 rpm for 20 minutes, add the amino graphene aqueous dispersion prepared in step 1, continue to stir for 20-30 minutes, add the nanocellulose dispersion prepared in step 1, continue to stir for 20 minutes, and obtain a mixed solution;

[0021] Step 4: adding hexamethylene diisocyanate to anhydrous ethanol, stirring and mixing evenly to obtain a 50-70wt% crosslinker solution; slowly adding the crosslinker solution to the mixed solution prepared in step 3, stirring at 300rpm for 30-40min after the addition is completed, evaporating and concentrating under reduced pressure to a solid content of 45-55%, and standing at room temperature for 1-2h to obtain a waterborne polyurethane wear-resistant coating;

[0022] Preferably, in step 4, the reduced pressure evaporation parameters are vacuum degree -0.08MPa to -0.09MPa, temperature 40 to 50°C, and stirring speed 300 to 500rpm.

[0023] The beneficial effects of the present invention are as follows:

[0024] This coating uses waterborne polyurethane as the main matrix, and by introducing components such as polytetrafluoroethylene (PTFE), fluorinated modified nano-silica, amino graphene, nanocellulose and hexamethylene diisocyanate (HDI) in the formula, a composite coating with super wear resistance, super hydrophobicity and high mechanical stability is collaboratively constructed. The present invention utilizes polytetrafluoroethylene (PTFE) and fluorinated modified silica to collaboratively construct a highly hydrophobic outer structure on the coating surface, significantly reducing the contact between moisture and the inside of the coating, and providing key protection for moisture-sensitive nanocellulose (CNF). Due to its ultra-low surface energy and low friction coefficient, polytetrafluoroethylene effectively reduces the adhesion of moisture and oil on the one hand, and enhances the wear resistance and scratch resistance of the coating on the other hand. Nano-silica is modified by fluorination, which effectively improves the hydrophobicity and anti-fouling ability of the surface, and also gives the coating better surface hardness and chemical inertness; fluoroalkyl can provide extremely low surface energy characteristics on the surface of nano-silica, enhance the synergistic effect with polytetrafluoroethylene, and make the coating surface present stable super-hydrophobic characteristics. Fluorinated modified silica further improves the surface hardness and antifouling ability of the coating by forming a dense hydrophobic network with polytetrafluoroethylene. The multi-layer hydrophobic barrier constructed blocks moisture from corroding nanocellulose, effectively avoiding the degradation of mechanical properties caused by moisture absorption of nanocellulose, and using hydrophobic interaction forces to prevent fiber aggregation, ensuring its uniform dispersion in the coating. Inside the coating, amino graphene and nanocellulose jointly form an efficient mechanical reinforcement network. The amino groups on the surface of amino graphene can form hydrogen bonds and covalent bonds with the waterborne polyurethane molecular chains, making the interfaces inside the coating more tightly bonded, thereby significantly improving the overall toughness and stability. At the same time, the amino graphene and nanocellulose also construct a multi-dimensional reinforcement network through the chemical reaction between the amino groups and the hydroxyl groups on the fiber surface, which plays a role in dispersing stress. When the coating is impacted or bent by external forces, it can effectively prevent stress concentration and reduce crack initiation and expansion. Hexamethylene diisocyanate (HDI) acts as a crosslinking agent, reacting with the hydroxyl groups in waterborne polyurethane to form a highly crosslinked three-dimensional network structure, effectively improving the hardness and chemical resistance of the coating, and further consolidating the interaction between the components by reacting with the residual amino groups on the surface of amino graphene and the possible active sites of fluorinated modified silica at the interface; this molecular-level crosslinking mechanism enables the coating to maintain stable performance in harsh environments such as high humidity, acid, alkali or organic solvents. In addition, nanocellulose uses its high specific surface area and certain functional groups to provide additional crosslinking points, and cooperates with amino graphene to construct a multi-level mechanical support structure, which significantly improves its comprehensive properties such as crack resistance, impact resistance and friction resistance while maintaining the flexibility of the coating.The abundant amino groups on the surface of aminated graphene form hydrogen bonds and covalent bonds with the molecular chains of waterborne polyurethane, significantly strengthening the interfacial bonding between the matrix and the graphene sheets; in addition, it can also chemically react with the hydroxyl groups on the surface of nanocellulose to achieve more effective stress transfer and dispersion, thereby improving toughness and impact resistance. Nanocellulose has a high specific surface area and a good fiber network structure, forming a synergistic reinforcement effect with aminated graphene, which can not only disperse stress and reduce crack formation under the action of external forces, but also maintain the flexibility and stability of the coating.

[0025] In summary, the present invention utilizes waterborne polyurethane to construct a stable main frame under the cross-linking action of HDI, polytetrafluoroethylene and fluorinated modified nano-silica form a durable super-hydrophobic and anti-fouling outer layer on the surface, and amino graphene and nano-cellulose provide strong mechanical support inside. The organic combination of each component enables the coating to achieve better impact resistance, chemical resistance and wear resistance. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the technical solutions in the present invention or the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings in the following description are only for the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 It is a graph showing the abrasion resistance test results of the waterborne polyurethane coatings prepared in Example 2 of the present invention and Comparative Examples 1 to 5;

[0028] Figure 2 It is a graph showing the mechanical strength test results of the waterborne polyurethane coatings prepared in Example 2 of the present invention and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0029] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them; based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. It should be noted that, unless otherwise specified, the raw materials involved in the present invention are purchased through conventional commercial channels.

[0030] Example 1: A waterborne polyurethane wear-resistant coating, comprising the following raw materials in parts by weight: 65 parts of waterborne polyurethane, 5 parts of polytetrafluoroethylene, 3 parts of fluorinated modified nano-silica, 2 parts of amino graphene, 2 parts of hexamethylene diisocyanate, 0.5 parts of emulsifier and 1 part of nano-cellulose.

[0031] The specific preparation steps of fluorinated modified nano-silica are as follows:

[0032] A1: Disperse 2 g of nano-silica in 100 mL of anhydrous ethanol, and disperse evenly by ultrasonic treatment to obtain a nano-silica dispersion; add 0.5 g of trifluoropropyltriethoxysilane to 20 mL of anhydrous ethanol, stir and mix evenly, adjust the pH to 5 with 0.1 M hydrochloric acid, and let stand for 30 min to obtain a silane solution;

[0033] A2: Slowly add 100 mL of the nano-silica dispersion prepared in step A1 into 3 mL of the silane solution, control the temperature at 40°C, stir and react for 6 hours, centrifuge, filter, wash alternately with anhydrous ethanol and deionized water for 3 times, and dry at 60°C for 24 hours to obtain fluorinated modified nano-silica;

[0034] The specific preparation steps of amination graphene are as follows:

[0035] B1: Disperse 1 g of graphene oxide in 100 mL of deionized water, disperse evenly by ultrasonic treatment, then add 8 mL of anhydrous ethanol, continue stirring for 10 min, and obtain a graphene oxide dispersion;

[0036] B2: Add 2 mL of ethylenediamine to 100 mL of graphene oxide dispersion prepared in step B1, adjust the pH to 11 with ammonia water, heat in a water bath to 80°C, stir and react for 6 hours. After the reaction is completed, cool naturally to room temperature, centrifuge, wash alternately with deionized water and anhydrous ethanol for 3 times, and dry at 60°C for 12 hours to obtain amino graphene;

[0037] The specific preparation steps of waterborne polyurethane wear-resistant coating are as follows:

[0038] Step 1: Disperse nanocellulose in deionized water, and ultrasonically disperse for 20 minutes to obtain a 3wt% nanocellulose dispersion; disperse polytetrafluoroethylene in deionized water, and ultrasonically disperse for 10 minutes to obtain a 30wt% polytetrafluoroethylene dispersion; add amino graphene to 90wt% ethanol solution, and ultrasonically disperse for 20 minutes to obtain a 1.5wt% amino graphene aqueous dispersion;

[0039] Step 2: Add the aqueous polyurethane to deionized water, dilute to 30wt% solid content, add 0.5wt% PEG-40 by weight of the aqueous polyurethane, stir for 10 minutes, and obtain an aqueous polyurethane system; slowly dropwise add the polytetrafluoroethylene dispersion prepared in step 1 to the aqueous polyurethane system, and stir at 300rpm for 20 minutes;

[0040] Step 3: After completing the operation in step 2, add fluorinated modified nano-silica, continue to stir at 300 rpm for 20 minutes, add the amino graphene aqueous dispersion prepared in step 1, continue to stir for 20 minutes, add the nanocellulose dispersion prepared in step 1, continue to stir for 20 minutes, and obtain a mixed solution;

[0041] Step 4: Add hexamethylene diisocyanate to anhydrous ethanol, stir and mix evenly to obtain a 50wt% crosslinker solution; slowly add the crosslinker solution to the mixed solution prepared in step 3. After the addition is completed, stir at 300rpm for 30min, and the reduced pressure evaporation parameters are vacuum degree -0.08MPaMPa, temperature 40°C, stirring speed 300rpm, concentrate to a solid content of 45%, and stand at room temperature for 1h to obtain a water-based polyurethane wear-resistant coating.

[0042] Example 2: A waterborne polyurethane wear-resistant coating, comprising the following raw materials in parts by weight: 70 parts of waterborne polyurethane, 8 parts of polytetrafluoroethylene, 5 parts of fluorinated modified nano-silica, 4 parts of amino graphene, 2.5 parts of hexamethylene diisocyanate, 0.8 parts of emulsifier and 2.5 parts of nano-cellulose.

[0043] The specific preparation steps of fluorinated modified nano-silica are as follows:

[0044] A1: Disperse 2 g of nano-silica in 180 mL of anhydrous ethanol, and disperse evenly by ultrasonic treatment to obtain a nano-silica dispersion; add 0.5 g of trifluoropropyltriethoxysilane to 25 mL of anhydrous ethanol, stir and mix evenly, adjust the pH to 4.5 with 0.1 M hydrochloric acid, and let stand for 30 min to obtain a silane solution;

[0045] A2: Slowly add 180 mL of the nano-silica dispersion prepared in step A1 into 8 mL of the silane solution, control the temperature at 50°C, stir and react for 5 hours, centrifuge, filter, wash alternately with anhydrous ethanol and deionized water for 3 times, and dry at 70°C for 20 hours to obtain fluorinated modified nano-silica;

[0046] The specific preparation steps of amination graphene are as follows:

[0047] B1: Disperse 1 g of graphene oxide in 150 mL of deionized water, disperse evenly by ultrasonic treatment, then add 10 mL of anhydrous ethanol, continue stirring for 10 min, and obtain a graphene oxide dispersion;

[0048] B2: Add 2 mL of ethylenediamine to 150 mL of graphene oxide dispersion prepared in step B1, adjust the pH to 10.5 with ammonia water, heat to 80°C in a water bath, stir and react for 7 hours. After the reaction is completed, cool naturally to room temperature, centrifuge, wash alternately with deionized water and anhydrous ethanol for 3 times, and dry at 60°C for 20 hours to obtain amino graphene;

[0049] The specific preparation steps of waterborne polyurethane wear-resistant coating are as follows:

[0050] Step 1: Disperse nanocellulose in deionized water, and ultrasonically disperse for 25 minutes to obtain a 4wt% nanocellulose dispersion; disperse polytetrafluoroethylene in deionized water, and ultrasonically disperse for 15 minutes to obtain a 35wt% polytetrafluoroethylene dispersion; add amino graphene to 90wt% ethanol solution, and ultrasonically disperse for 25 minutes to obtain a 2wt% amino graphene aqueous dispersion;

[0051] Step 2: Add the aqueous polyurethane to deionized water, dilute to 35wt% solid content, add 1.5wt% Tween-20 by weight of the aqueous polyurethane, stir for 10 minutes, and obtain an aqueous polyurethane system; slowly dropwise add the polytetrafluoroethylene dispersion prepared in step 1 to the aqueous polyurethane system, and stir at 400rpm for 20 minutes;

[0052] Step 3: After completing the operation in step 2, add fluorinated modified nano-silica, continue to stir at 400 rpm for 20 minutes, add the amino graphene aqueous dispersion prepared in step 1, continue to stir for 25 minutes, add the nanocellulose dispersion prepared in step 1, continue to stir for 20 minutes, and obtain a mixed solution;

[0053] Step 4: Add hexamethylene diisocyanate to anhydrous ethanol, stir and mix evenly to obtain a 60wt% crosslinker solution; slowly add the crosslinker solution to the mixed solution prepared in step 3. After the addition is completed, stir at 300rpm for 35min, and the reduced pressure evaporation parameters are vacuum degree -0.08MPaMPa, temperature 45°C, stirring speed 400rpm, concentrate to a solid content of 50%, and stand at room temperature for 2h to obtain a water-based polyurethane wear-resistant coating.

[0054] Example 3: A water-based polyurethane wear-resistant coating, comprising the following raw materials in parts by weight: 75 parts of water-based polyurethane, 10 parts of polytetrafluoroethylene, 6 parts of fluorinated modified nano-silica, 5 parts of amino graphene, 3 parts of hexamethylene diisocyanate, 1 part of emulsifier and 3 parts of nano-cellulose.

[0055] The specific preparation steps of fluorinated modified nano-silica are as follows:

[0056] A1: Disperse 2 g of nano-silica in 200 mL of anhydrous ethanol, and disperse evenly by ultrasonic treatment to obtain a nano-silica dispersion; add 0.5 g of trifluoropropyltriethoxysilane to 30 mL of anhydrous ethanol, stir and mix evenly, adjust the pH to 4 with 0.1 M hydrochloric acid, and let stand for 30 min to obtain a silane solution;

[0057] A2: Slowly add 200 mL of the nano-silica dispersion prepared in step A1 into 10 mL of the silane solution, control the temperature at 60°C, stir and react for 4 hours, centrifuge, filter, wash alternately with anhydrous ethanol and deionized water for 3 times, and dry at 80°C for 12 hours to obtain fluorinated modified nano-silica;

[0058] The specific preparation steps of amination graphene are as follows:

[0059] B1: Disperse 1 g of graphene oxide in 120 mL of deionized water, disperse evenly by ultrasonic treatment, then add 9 mL of anhydrous ethanol, continue stirring for 10 min, and obtain a graphene oxide dispersion;

[0060] B2: Add 2 mL of ethylenediamine to 120 mL of graphene oxide dispersion prepared in step B1, adjust the pH to 11 with ammonia water, heat to 80°C in a water bath, stir and react for 8 hours. After the reaction is completed, cool naturally to room temperature, centrifuge, wash alternately with deionized water and anhydrous ethanol for 3 times, and dry at 60°C for 24 hours to obtain amino graphene;

[0061] The specific preparation steps of waterborne polyurethane wear-resistant coating are as follows:

[0062] Step 1: Disperse nanocellulose in deionized water, and ultrasonically disperse for 30 minutes to obtain a 5wt% nanocellulose dispersion; disperse polytetrafluoroethylene in deionized water, and ultrasonically disperse for 20 minutes to obtain a 40wt% polytetrafluoroethylene dispersion; add amino graphene to 90wt% ethanol solution, and ultrasonically disperse for 30 minutes to obtain a 1.8wt% amino graphene aqueous dispersion;

[0063] Step 2: Add the waterborne polyurethane into deionized water, dilute to 40 wt% solid content, add 2 wt% sodium dodecylbenzene sulfonate, stir for 10 min, and obtain a waterborne polyurethane system; slowly drop the polytetrafluoroethylene dispersion prepared in step 1 into the waterborne polyurethane system, and stir at 500 rpm for 20 min;

[0064] Step 3: After completing the operation in step 2, add fluorinated modified nano-silica, continue to stir at 500 rpm for 20 minutes, add the amino graphene aqueous dispersion prepared in step 1, continue to stir for 30 minutes, add the nanocellulose dispersion prepared in step 1, continue to stir for 20 minutes, and obtain a mixed solution;

[0065] Step 4: Add hexamethylene diisocyanate to anhydrous ethanol, stir and mix evenly to obtain a 70wt% cross-linker solution; slowly add the cross-linker solution to the mixed solution prepared in step 3. After the addition is completed, stir at 300rpm for 40min, and the reduced pressure evaporation parameters are vacuum degree -0.08MPaMPa, temperature 50°C, stirring speed 500rpm, concentrate to a solid content of 55%, and stand at room temperature for 1h to obtain a water-based polyurethane wear-resistant coating.

[0066] Comparative Example 1: The operation of Comparative Example 1 is substantially the same as that of Example 2, except that polytetrafluoroethylene is not added in Comparative Example 1.

[0067] Comparative Example 2: The operation of Comparative Example 2 is basically the same as that of Example 2, except that no fluorinated modified nano-silica is added in Comparative Example 2.

[0068] Comparative Example 3: The operation of Comparative Example 3 is substantially the same as that of Example 2, except that no amino graphene is added in Comparative Example 3.

[0069] Comparative Example 4: The operation of Comparative Example 4 is basically the same as that of Example 2, except that nanocellulose is not added in Comparative Example 4.

[0070] Comparative Example 5: The operation of Comparative Example 5 is substantially the same as that of Example 2, except that polytetrafluoroethylene and fluorinated modified silica are not added in Comparative Example 5.

[0071] Performance Test:

[0072] Hydrophobicity test: The waterborne polyurethane coatings prepared in the above Examples 1 to 3 and Comparative Examples 1 to 5 were subjected to contact angle tests. The waterborne polyurethane coatings were coated on a glass plate with a thickness of 80 μm. After curing, the samples were cut into circular samples with a diameter of 100 mm for testing. A contact angle greater than 140° was recorded as A, a contact angle between 130 and 140° was recorded as B, and a contact angle less than 130° was recorded as C. All samples were tested at room temperature and a humidity of 50%. A 5 μL water droplet was used for each test. To ensure data reliability, 5 contact angle measurements were performed for each sample, and the average value was taken as the final result. The test results are shown in Table 1.

[0073] Hydrophobic stability test: The test steps are basically the same as above. The test conditions are divided into four types. The first is to immerse in 3.5% NaCl solution and test at room temperature; the second is to test at high temperature of 85°C and humidity of 70%; the third is to test at 95% humidity and room temperature; the fourth is to test at room temperature, humidity of 70%, and ultraviolet irradiation UV intensity of 0.5W / m 2 The test time is 168 hours. The test results are shown in Table 1.

[0074] Table 1. Test results of hydrophobicity and stability of waterborne polyurethane

[0075]

[0076]

[0077] It can be seen from the results in Table 1 that the waterborne polyurethane coating prepared by the present invention has excellent hydrophobicity through the synergistic effect of multiple substances. It can be seen from the results of Example 2 and Comparative Example 1, Comparative Example 2 and Comparative Example 5 that polytetrafluoroethylene and fluorinated modified nano-silica can effectively construct a super-hydrophobic surface and achieve super-hydrophobic properties of the coating; it can be seen from the results of Comparative Example 1 and Example 2 that the absence of polytetrafluoroethylene significantly reduces the overall hydrophobicity of the coating. Under high salt solution and high humidity conditions, the lack of polytetrafluoroethylene protection significantly reduces the hydrophobicity of the coating; from the results of Comparative Example 2 and Example 2 It can be seen that the absence of fluorinated modified nano-silica reduces the hydrophobicity of the coating. Although polytetrafluoroethylene is still present, the lack of the synergistic effect of fluorinated silica makes it impossible to form a dense hydrophobic network, and the hydrophobicity is affected. In a high salt and high humidity environment, polytetrafluoroethylene alone cannot completely maintain super hydrophobicity, resulting in the hydrophobicity being affected. From the results of Comparative Example 1, Comparative Example 2 and Example 2, it can be seen that nanocellulose may agglomerate due to the lack of hydrophobicity, thereby increasing the roughness of the coating, and may cause the agglomerated area to become a weak point for chemical corrosion, thereby reducing the chemical stability.

[0078] Abrasion resistance test: The waterborne polyurethane coatings prepared in Example 2 and Comparative Examples 1 to 5 were coated on a glass plate with a thickness of 80 μm. After curing, the samples were cut into circular samples with a diameter of 100 mm. A 500 g weight was used to grind the samples at a speed of 60 rpm for 500 and 1000 turns. The mass change before and after the test was measured. Abrasion loss = (mass before test - mass after test) / mass before test × 100%. The results are shown in FIG. Figure 1 shown.

[0079] Depend on Figure 1As can be seen from the results, the waterborne polyurethane prepared by the present invention has excellent wear resistance; from the results of Comparative Example 1 and Example 2, it can be seen that the absence of polytetrafluoroethylene directly leads to an increase in the friction coefficient and aggravated surface wear. Although the fluorinated modified nano-silica can provide a certain hardness, the synergy is significantly affected; from the results of Comparative Example 2 and Example 2, it can be seen that after the lack of fluorinated modified nano-silica, the surface hardness of the coating decreases, the scratch damage increases, and polytetrafluoroethylene alone cannot provide sufficient hardness, which leads to a decrease in wear resistance; from the results of Comparative Example 3 and Example 2, it can be seen that the lack of amino-modified graphene, The mechanical strengthening effect is weakened, but the surface properties are maintained by polytetrafluoroethylene and fluorinated modified nano-silica. The short-term wear resistance is slightly low, and the performance decreases significantly after long-term wear. It can be seen from the results of Comparative Example 4 and Example 2 that the wear resistance is relatively low in a short period of time due to the surface components polytetrafluoroethylene and fluorinated nano-silica. During long-term high-load wear, the crack propagation increases and the durability is significantly affected. It can be seen from the results of Comparative Example 5 and Example 2 that the wear-resistant core component is missing, the surface hardness and friction coefficient are seriously damaged, the wear loss is obvious, and the coating is more susceptible to mechanical grinding, resulting in significant quality damage.

[0080] Mechanical strength test: The waterborne polyurethane coating prepared in Example 2 and Comparative Examples 1 to 5 was coated on a polyester film with a thickness of 100 μm and cut into pieces of 150 mm long and 20 mm wide. The tensile strength and elongation at break were tested using a universal material testing machine. The results are as follows: Figure 2 shown.

[0081] Depend on Figure 2 As a result, the waterborne polyurethane coating prepared by the present invention has extremely high tensile strength and excellent elongation at break, showing excellent mechanical properties; from the results of comparative example 1 and example 2, it can be seen that the absence of polytetrafluoroethylene increases the surface friction, cracks are more likely to expand under high strain conditions, and the elongation at break is slightly reduced; from the results of comparative example 2 and example 2, it can be seen that after the lack of fluorinated modified nano-silica, the hardness of the coating is slightly reduced, but the effect on the mechanical strength is small; from the results of comparative example 3 and example 2, it can be seen that the absence of amino graphene leads to insufficient interface bonding force, an increase in crack initiation points, and a significant decrease in the tensile strength of the coating. The absence of the sheet support of amino graphene causes the cracks to expand faster under strain conditions, and the elongation is greatly reduced; from the results of comparative example 4 and example 2, it can be seen that after the lack of nanocellulose, the stress dispersion ability of the coating is weakened, the crack expansion increases, and the elongation at break is significantly reduced; from the results of comparative example 5 and example 2, it can be seen that the coating lacks an effective multi-dimensional reinforcement structure, the cracks expand rapidly during the stretching process, and the toughness is greatly reduced.

[0082] Adhesion test: The waterborne polyurethane coatings prepared in Example 2 and Comparative Examples 1 to 5 were coated on a glass plate and cured to form a coating. A 2 mm grid was used to draw 10×10 grid lines on the surface of the coating. The coating was then placed at 85° C. and a humidity of 90% for 72 hours before testing. An adhesive tape was attached to the grid surface, pressed and quickly torn off. The shedding of the coating in the grid was recorded, which was divided into 0 to 5 levels (0: no shedding; 1: the shedding portion was less than 5%; 2: the shedding portion was 5-15%; 3: the shedding portion was 15-35%; 4: the shedding portion was 35-65%; 5: the shedding portion was greater than 65%). The results are shown in Table 2 below.

[0083] Table 2. Waterborne polyurethane adhesion test results

[0084] sample Example 2 Comparative Example 1 Comparative Example 2 Comparative Example 3 Comparative Example 4 Comparative Example 5 Adhesion Level 0 Level 2 Level 2 Level 3 Level 2 Level 4

[0085] It can be seen from the results in Table 2 that the hydrophobic outer layer of the waterborne polyurethane prepared by the present invention effectively blocks the influence of moisture on the internal material and has excellent adhesion performance; it can be seen from the results of Comparative Example 1, Comparative Example 2 and Example 2 that the lack of the ultra-dense hydrophobic structure layer synergistically constructed by polytetrafluoroethylene and fluorinated modified nano-silica may increase the possibility of moisture intrusion, reduce the coating interface bonding force, and further increase the local shedding area, while the lack of fluorinated modified nano-silica may lead to a decrease in surface hardness, moisture accelerated cracking, and moisture intrusion caused the agglomeration of nanofibers, resulting in an increase in surface roughness, which also had an effect on adhesion. It has a certain degree of influence; from the results of Comparative Example 3 and Example 2, it can be seen that in the absence of amino graphene, the interfacial bonding force is significantly reduced, the high humidity conditions aggravate the crack propagation, the mechanical support effect of nanocellulose is also weakened due to insufficient interfacial bonding force, the synergy is significantly reduced, and the adhesion is significantly reduced; from the results of Comparative Example 3 and Example 2, it can be seen that in the absence of nanocellulose, the internal reinforcement network is incomplete and the adhesion is affected to a certain extent; from the results of Comparative Example 5 and Example 2, it can be seen that the outer hydrophobic coating is missing, the coating completely loses its protection against moisture, the moisture absorption and agglomeration of nanocellulose are aggravated, the local crack propagation is out of control, and the adhesion is greatly reduced.

[0086] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A waterborne polyurethane wear-resistant coating, characterized in that: The composition comprises the following raw materials in parts by weight: 65-75 parts of waterborne polyurethane, 5-10 parts of polytetrafluoroethylene, 3-6 parts of fluorinated modified nano silicon dioxide, 2-5 parts of amino graphene, 2-3 parts of hexamethylene diisocyanate, 0.5-1 part of emulsifier and 1-3 parts of nano cellulose.

2. A waterborne polyurethane wear-resistant coating according to claim 1, characterized in that: The emulsifier is any one of Tween-20, sodium dodecylbenzene sulfonate and PEG-40.

3. A waterborne polyurethane wear-resistant coating according to claim 2, characterized in that: The specific preparation steps of the fluorinated modified nano-silica are as follows: A1: Disperse nano-silicon dioxide in anhydrous ethanol, disperse evenly by ultrasonic treatment, and obtain nano-silicon dioxide dispersion; add trifluoropropyltriethoxysilane to anhydrous ethanol, stir and mix evenly, adjust the pH with hydrochloric acid, and let stand to obtain a silane solution; A2: Slowly add the nano-silica dispersion prepared in step A1 into the silane solution, control the temperature at 40-60° C., stir the reaction, centrifuge, filter, alternately wash with anhydrous ethanol and deionized water, and dry to obtain fluorinated modified nano-silica.

4. A waterborne polyurethane wear-resistant coating according to claim 3, characterized in that: In step A1, the ratio of the amount of the nano-silica to anhydrous ethanol is 20 mg: 1-2 mL; the ratio of the amount of the trifluoropropyltriethoxysilane to anhydrous ethanol is 1 g: 20-30 mL; in step A2, the volume ratio of the nano-silica dispersion to the silane solution is 100: 3-5.

5. A waterborne polyurethane wear-resistant coating according to claim 4, characterized in that: The specific preparation steps of the amino graphene are as follows: B1: Disperse graphene oxide in deionized water, disperse it evenly by ultrasonic treatment, then add anhydrous ethanol, continue stirring to obtain a graphene oxide dispersion; B2: Add ethylenediamine to the graphene oxide dispersion prepared in step B1, adjust the pH with ammonia water, heat in a water bath, stir to react, and after the reaction is completed, naturally cool to room temperature, centrifuge, wash alternately with deionized water and anhydrous ethanol, and dry to obtain amino graphene.

6. A waterborne polyurethane wear-resistant coating according to claim 5, characterized in that: In step B1, the ratio of the amount of graphene oxide, deionized water and anhydrous ethanol is 1g:100-150mL:8-10mL; in step B2, the volume ratio of the graphene oxide dispersion and ethylenediamine is 10-15:

2.

7. A method for preparing a waterborne polyurethane wear-resistant coating according to any one of claims 1 to 6, characterized in that: The specific preparation steps are as follows: Step 1: dispersing nanocellulose in deionized water, and performing ultrasonic dispersion treatment to obtain nanocellulose dispersion liquid; dispersing polytetrafluoroethylene in deionized water, and performing ultrasonic dispersion treatment to obtain polytetrafluoroethylene dispersion liquid; adding amino graphene to ethanol solution, and performing ultrasonic dispersion treatment to obtain amino graphene aqueous dispersion liquid; Step 2: adding waterborne polyurethane to deionized water, diluting, adding emulsifier, stirring, and obtaining a waterborne polyurethane system; slowly dropping the polytetrafluoroethylene dispersion prepared in step 1 into the waterborne polyurethane system, stirring; Step 3: After completing the operation in step 2, add fluorinated modified nano-silica, continue stirring, add the amino graphene aqueous dispersion prepared in step 1, continue stirring, add the nanocellulose dispersion prepared in step 1, continue stirring to obtain a mixed solution; Step 4: adding hexamethylene diisocyanate to anhydrous ethanol, stirring and mixing evenly to obtain a crosslinking agent solution; The crosslinking agent solution is slowly added to the mixed solution prepared in step three. After the addition is completed, the mixture is stirred, concentrated by evaporation under reduced pressure, and allowed to stand at room temperature to obtain a waterborne polyurethane wear-resistant coating.

8. The method for preparing a waterborne polyurethane wear-resistant coating according to claim 7, characterized in that: In step 4, the reduced pressure evaporation parameters are vacuum degree -0.08MPa to -0.09MPa, temperature 40 to 50°C, and stirring speed 300 to 500rpm.

Citation Information

Patent Citations

  • Preparing method of graphene / waterborne polyurethane composite material

    CN104861643A

  • Wear-resistant high-adhesion super-hydrophobic coating and preparation method thereof

    CN113292898A

  • Composite wear-resistant waterborne polyurethane emulsion and preparation method thereof

    CN114350242A

  • Preparation method of super-hydrophobic coating with high wear resistance and water impact resistance

    CN117050563A

  • Flame-retardant waterborne polyurethane coating as well as preparation method and application thereof

    CN118995030A

Cited By

  • Flame-retardant antistatic high-molecular coating material for dust-free workshop terrace

    CN120665498A